Investigation of self-healing process and strength of biopolymer-stabilized silty sand: Comparison of Xanthan and Persian gum in geotechnical engineering - Farhad Askari; Mehdi Gharib; Nima Ranjbar Malidarreh; Mojtaba Esmaeilnia Amiri; Saman Soleimani Kutanaei (Carbohydrate Polymer Technologies and Applications, 2025)
This study investigates the self-healing behavior and strength development of silty sand stabilized with two natural biopolymers: Persian gum (PG), a plant-based biopolymer with a relatively linear structure, and Xanthan gum (XG), a microbially derived biopolymer with a branched molecular structure. The biopolymers were used at contents of 0.5 %, 1 %, and 2 % by dry weight of soil. Cylindrical samples were cured under different conditions and then intentionally damaged to evaluate healing after 7, 28, and 90 days. Mechanical performance was assessed using unconfined compressive strength (UCS) and ultrasonic pulse velocity (UPV), and microstructural changes were examined via SEM and AFM. Results showed that the highest strength gains occurred with 2 % biopolymer content after 28 days of curing. UCS reached 950 kPa for PG and 1193.6 kPa for XG. XG-stabilized samples showed greater healing capacity (38 % UCS recovery after 90 days) but also higher strength loss over time. PG, while offering slightly lower strength, provided more stable performance and lower sensitivity to moisture-induced damage. A strong correlation (R² = 0.9561) was observed between UCS and UPV, confirming UPV as a reliable non-destructive method for assessing self-healing. Overall, PG is proposed as a sustainable and effective alternative for long-term stabilization of silty sands.